Comparison of Design Options for Encapsulated Solvent Processes for CO2 Capture. (July 2017) - Raksajati, A.; Ho, M.T.; Wiley, D.E.
Abstract: Encapsulated solvents are one of the new absorption processes currently under development for CO2 capture. In an encapsulated solvent system, the operating solvent fluid is enclosed in a thin membrane while the working fluid is enclosed in a membrane capsule. In this system, a significantly higher surface area is provided compared to conventional packing. This paper presents the results of a scoping level techno-economic assessment of encapsulated solvent systems for post-combustion CO2 capture. Two process configurations are evaluated; the first uses fixed-bed columns for the absorber and regenerator, while the second uses a circulated fluidized bed as the absorber and a bubbling fluidized bed as the regenerator. The capture and capital costs for using an encapsulated MEA 30% wt. solvent system were found to be double that of for using MEA solvent in a conventional packed-column, while the regeneration duty was about one and half times higher. This is because the membrane resistance of the encapsulated system increases the regeneration energy required and the higher capital costs for the extra unit operations required.